2012
DOI: 10.1007/s12031-012-9801-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroplastin Expression in the Hippocampus of Mice Lacking Complex Gangliosides

Abstract: We report changes in neuroplastin gene and protein expression in the hippocampus of B4galnt1 null mice, which lacks complex ganglioside structures, compared with that of wild-type mice. Neuroplastin mRNA expression was significantly higher in the hippocampi of B4galnt1 null mice than in wild-type mice. Moreover, Western blot analysis shows increased neuroplastin protein levels of neuroplastin-55 isoform in B4galnt1 null hippocampal homogenates. Immunohistochemistry revealed a substantially different distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Interestingly, Neuroplastin expression is linked to the ganglioside composition of neural membranes (Mlinac et al 2012). In mice deficient for the enzyme B4galnt1 and thus lacking complex gangliosides, Neuroplastin mRNA and particularly Np55 protein expression is increased in the hippocampus.…”
Section: Developmental Profile Of the Neuroplastins In Brainmentioning
confidence: 99%
“…Interestingly, Neuroplastin expression is linked to the ganglioside composition of neural membranes (Mlinac et al 2012). In mice deficient for the enzyme B4galnt1 and thus lacking complex gangliosides, Neuroplastin mRNA and particularly Np55 protein expression is increased in the hippocampus.…”
Section: Developmental Profile Of the Neuroplastins In Brainmentioning
confidence: 99%
“…Our group reported that Np positioning within the neuronal membrane is highly sensitive on its particular membrane lipid environment in murine brain tissue [30]. Specifically, compositional changes of membrane glycosphingolipids-gangliosides alter Np gene and protein expression, as well its immunolocalization and distribution in the mouse hippocampus [30]. The finding that implies effects of membrane lipid composition on functionality of Np has been recently supported by a study describing specific rearrangements of Np and gangliosides upon chronic stress and aging in the rat hippocampus [31].…”
Section: Neuroplastin Discovery Structure and Functionsmentioning
confidence: 99%
“…Further aspect of molecular complexity and machineries underlying processes related to memory, learning, and cognition encompasses so far a well-recognized influence of neuronal membrane composition, organization, and dynamics on synaptic plasticity [28,29]. Our group reported that Np positioning within the neuronal membrane is highly sensitive on its particular membrane lipid environment in murine brain tissue [30]. Specifically, compositional changes of membrane glycosphingolipids-gangliosides alter Np gene and protein expression, as well its immunolocalization and distribution in the mouse hippocampus [30].…”
Section: Neuroplastin Discovery Structure and Functionsmentioning
confidence: 99%
“…In the human brain, and very similarly in the rodent brain (Figure 2), GM1, GD1a, GD1b, and GT1b together sum up to 97% of the total ganglioside content. Ganglioside distribution has been studied in brain tissue using specific primary antibodies followed by 3-3′-Diaminobenzidine-based staining similarly as for Thy-1 (Heffer-Lauc et al, 2005, 2007) or other CAMs like Neuroplastin (Mlinac et al, 2012; Herrera-Molina et al, 2017; Ilic et al, 2019). However, special caution is required regarding the detergent used during the procedures as inappropriate conditions produce artifacts as drastic as loss and re-distribution of several ganglioside types.…”
Section: Brief Overview On Neuronal Gangliosidesmentioning
confidence: 99%